2014
DOI: 10.1002/2014jc009862
|View full text |Cite
|
Sign up to set email alerts
|

Long-term annual primary production in the Ulleung Basin as a biological hot spot in the East/Japan Sea

Abstract: Although the Ulleung Basin is an important biological ''hot spot'' in East/Japan Sea (hereafter the East Sea), very limited knowledge for seasonal and annual variations in the primary productivity exists. In this study, a recent decadal trend of primary production in the Ulleung Basin was analyzed based on MODIS-derived monthly primary production for a better annual production budget. Based on the MODISderived primary production, the mean daily primary productivity was 766. the Ulleung Basin during the study p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 21 publications
(81 reference statements)
2
52
1
Order By: Relevance
“…Recently, Jo et al [40] reported that the rate of the SST increase was 0.041˝C¨y´1 in the east coast of Korea, which was much faster than the global average (0.005˝C¨y´1). However, no substantial increased SST was observed in this study during our investigation period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), most likely because the observation period was not long enough to detect any small changes in the SST [13]. Gregg et al [39] argued that increased temperature and shallower mixed layers via surface stratification could result in increased Chl-a concentrations in early spring and that more severe nutrient exhaustion in late spring and summer could reduce the Chl-a concentrations and, consequently, annual primary production [41].…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 55%
See 4 more Smart Citations
“…Recently, Jo et al [40] reported that the rate of the SST increase was 0.041˝C¨y´1 in the east coast of Korea, which was much faster than the global average (0.005˝C¨y´1). However, no substantial increased SST was observed in this study during our investigation period (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012), most likely because the observation period was not long enough to detect any small changes in the SST [13]. Gregg et al [39] argued that increased temperature and shallower mixed layers via surface stratification could result in increased Chl-a concentrations in early spring and that more severe nutrient exhaustion in late spring and summer could reduce the Chl-a concentrations and, consequently, annual primary production [41].…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 55%
“…Gregg et al [39] argued that increased temperature and shallower mixed layers via surface stratification could result in increased Chl-a concentrations in early spring and that more severe nutrient exhaustion in late spring and summer could reduce the Chl-a concentrations and, consequently, annual primary production [41]. In fact, the concentrations of major inorganic nutrients decreased in euphotic water layers (0-50 m water depth) in the Ulleung Basin (located in the middle of the East Sea) during our observation period [13]. The decrease in nitrate concentrations was also distinct during both the summer time and the winter season in the study region from 2003 to 2012 [13].…”
Section: Long-term Pattern Of the Annual Primary Production In The Eamentioning
confidence: 74%
See 3 more Smart Citations